Making Quality Improvement Happen in the Real World: Building Capability and Improving Multiple Projects at the Same Time. Issue 1 (7th April 2016) - Daniel, Malcolm; Puxty, Alex; Miles, Barbara
Abstract : Improving work as part of clinical practice is challenging. Plans for improvement are often made, but not followed through. A recent experience of failure in an ICU led to a change in approach. Members of the multi-professional team committed to meet weekly to learn about quality improvement by working on improvement projects. The group selected four topics they wanted to work on. These were: a bundle for patients admitted with septic shock; early (≤4 hours) sedation vacation after admission to ICU to allow titration of sedation to effect; achieving ≥ 20 minutes of mobilisation per day in ventilated patients; and medicines reconciliation. This quality improvement meeting was built into another regular weekly meeting. Initially the meeting ran for 30 minutes; each week some focused quality improvement teaching was provided in addition to talking about each individual project. The team found the meeting useful, they saw the progress they were making but felt the allotted time was too short. After 6 weeks, the initial early results persuaded the team to increase the duration of this meeting to 45 minutes. At the start reliability of each process was low (between 10% and 38%). All four projects achieved their stated process reliability aim. This took between 165 and 334 days for each project. Many tests of change ideas were required to achieve this. We have been able to improve multiple topics in a short period and produce sustainable change. The weekly meeting provided the focus to this improvement work. The teaching and coaching on quality improvement methodology that occurred as part of this meeting helped accelerate our rate of progress. We believe this experience and the learning we have gained will help provide ideas for others who also want to improve healthcare delivery in different settings.